Gender Differences in Semantic Fluency Patterns in Children - Soriano, Federico; Fumagalli, Julieta; Shalom, Diego; Barreyro, Juan Pablo; Martínez-Cuitiño, Macarena (Lesya Ukrainka Eastern European National University, 2016)
Previous literature in cognitive psychology has provided data involving differences in language processing between men and women. It has been found that women are usually more proficient with certain semantic categories such as fruit, vegetables and furniture. Men are reported to be better at other categories semantic, e.g. tools and transport. The aim of this article is to provide an inquiry about possible differences in semantic category processing of living things (LT) and inanimate objects (IO) by Argentinian Spanish-speakers school-aged children. The group of 86 children between 8 and 12 years old (51.16% boys) has been assessed on a semantic fluency task. Six semantic categories have been tested, three of them from the LT domain (animals, fruit/vegetables, and body parts) and three from the IO domain (transport, clothes and musical instruments). Results showed differences in semantic processing between boys and girls. Girls retrieved more items from the LT domain and activated more animals and fruit/vegetables. These findings appear to support an innate conceptual organization of the mind, which is presumably influenced by cultural factors and/or schooling. Згідно з даними досліджень у галузі когнітивної психології, існують відмінності в переробленні мовних даних чоловіками та жінками. Виявлено, що жінки, як правило, більш вправні в певних семантичних категоріях, як-от: фрукти, овочі та меблі. Чоловіки ж краще за жінок орієнтуються в таких семантичних категоріях: інструменти та транспорт. У статті йдеться про експеримент, який проведено серед аргентинських дітей – носіїв іспанської мови, що полягав у визначенні можливих гендерних відмінностей під час виконання завдання на семантичну біжучість, а саме в категоріях з розряду істот та неістот. В експерименті взяла участь група з 86 дітей віком від 8 до 12 років (51,16 % хлопчиків), яким було запропоновано шість семантичних категорій, три з яких із розряду істот (тварини, фрукти/овочі, частини тіла), та три з розряду неістот (транспорт, одяг та музичні інструменти). Було зафіксовано генедрні відмінності у виконанні мовних завдань на основі різних семантичних категорій. Респонденти жіночої статі надали більшу кількість слів у категоріях істот, а саме: тварин, фруктів та овочів. Одержані дані засвідчують вроджену концептуальну організацію розуму, на який, імовірно, здатні впливати культурні чинники і/або навчання.
Keywords: school-age children; gender differences; semantic processing; living things; inanimate objects; діти шкільного віку; гендерні відмінності; семантична обробка; живі істоти; неістоти